Allergic Reaction Following Insertion of Vancomycin Loaded in Bone Cement - KL, Goh; MY, Nazri; CL, Ong (IIUM Medical Journal Malaysia, 2014)
Vancomycin bead is an important ancillary treatment for osteomyelitis caused by methicillin-resistant Staphylococcus aureus (MRSA). However, red-man syndrome, which can be a life-threatening complication of vancomycin, may occur from the use of vancomycin beads albeit rarely. We report our first case of red-man syndrome caused by vancomycin bead's insertion for chronic osteomyelitis. Symptomatic treatment was not effective and removal of the vancomycin beads seems to be the best treatment for this condition.